longitudinal study of the brain in healthy volunteers under stress caused by the pandemic of the new coronavirus infection COVID-19 - N. Yu. Safonova; N. I. Ananyeva; L. V. Lukina (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Relevance: The COVID-19 pandemic is a global process that has an extremely negative impact on the psychological state of people, which increases the level of anxiety, distress, and other reactive states. The impact of SARS-CoV-2 infection on the human nervous system and psyche is being actively studied. This study aimed to compare neuroimaging data in healthy individuals during the COVID-19 pandemic during 6 months of follow-up.Materials and methods: The initial model for comparing morphometric parameters was the «Central Nervous System Norm Bank», which includes MRI data of the brain of 131 healthy volunteers aged 20 to 70 years (including 72 women and 59 men), collected before the start of the pandemic COVID-19 and brain re-examination data six months later.Results: The voxel-based morphometry data we obtained do not match the morphometry data for PTSD and anxiety disorder. This probably reflects the more widespread nature of changes in the brain associated with COVID-19 and caused by the duration of the pandemic, changes in people’s lifestyle and thinking, and a state of uncertainty. Thus, the morphometric data show the neuroplasticity of the brain of adult healthy volunteers. These changes underline the need to reduce stress levels in healthy people during the pandemic, which can be implemented through the provision of convincing and reliable information about this disease.Conclusions: It would be additionally relevant to create opportunities for psycho prophylaxis, stress relief, which certainly increases the load on the psychotherapeutic service in a pandemic.